Peran Media Pembelajaran Guru Pendidikan Anak Usia Dini (PAUD) di Provinsi Jambi - Mahyudin Mahyudin (Universitas Batanghari Jambi, 2020)
The media is very instrumental and has a strategic function that directly or indirectly can affect motivation, interest and attention for young children in learning. The purpose of this study was to determine the role of PAUD teacher learning media in Jambi Province. The method used is descriptive quantitative cluster sampling technique, in this case the District and City in Jambi Province as the cluster. The number of early childhood education units (schools) include TK / RA, KB, TPA, and SPS, totaling 7,584. Then every District and City was selected by 10% randomly PAUD teachers from each school. So the number of samples was 758. The research instrument was a questionnaire or Media Perception Evaluation Scale (MPES) questionnaire containing 28 question items. Data for all parameters using a Microsoft Excel database. Pearson correlation was used to study the correlation between variables and independent t-test was used to compare groups with SPSS version 22. All statistical analyzes were carried out at a significance level of 5% and P <0.05 was considered statistically significant. The results of the study show that learning media plays an important role in the learning process for PAUD children in Jambi Province. As a result 59.6% answered strongly agree. Through the SPSS analyst results where the most influential visual media statements in PAUD teacher learning in Jambi province are statements 18,19,20,21 and 22 where 100% stated that visual media can provide motivation, whereas statements that had no effect were statements 17 where only 50.4% stated that visual media can provide motivation. It can be concluded that the use of learning media in early childhood is very instrumental to motivate, stimulate, explore and experiment.